Impact of daily wearing of fabric gloves on the management of hand eczema: A pilot study in health‐care workers - Kuwatsuka, Sayaka; Kuwatsuka, Yutaka; Tomimura, Saori; Takenaka, Motoi; Terasaka, Yoko; Izumikawa, Koichi; Morinaga, Yoshitomo; Yanagihara, Katsuori; Murota, Hiroyuki (Journal of dermatology, 2021)
Hand eczema is a major occupational disease, especially in medical workers, reducing their quality of life (QOL) and work productivity. Daily wearing of fabric gloves to prevent loss of moisture and lipids from the surface of the hands has been regarded as good in the management of hand eczema. However, limited evidence is available regarding the efficacy of moisturizing care with daily gloves on hand eczema. This pilot study was performed to evaluate the efficacy of moisturizing intervention with daily wearing of fabric gloves on skin barrier function, disease severity, and microbiome in health‐care workers with hand eczema. Study 1: Nurses in the neonatal intensive care unit or growing care unit with and without hand eczema were recruited in the study. Subjects were instructed to apply moisturizer and wear two types of fabric gloves, common cotton gloves and moisturizing fabric gloves containing malate, for 4 weeks. Study 2: Physicians and health‐care workers were recruited and instructed to wear a cotton glove on one hand at nighttime for 4 weeks. Disease severity, skin barrier function, QOL, and hand microbiome (Study 1) were evaluated. Study 1 found that daily wearing of both types of fabric gloves accompanied by use of topical moisturizers reduced the severity of hand eczema without changing the variation of microbiome. Study 2 found no apparent change between wearing and not wearing cotton gloves. In summary, topical moisturizer is of fundamental importance, and concomitant use of fabric gloves may merely enhance the efficacy of moisturizer in the management of hand eczema.